Situational analysis among therapy practitioners in autism rehabilitation centres in Perlis: a preliminary study - Nik Abdullah, Nik Md. Saiful Azizi; Sani, Badariah; Badzis, Mastura; Fatah Yasin, Mohammad Dhiya’ul Hafidh (Human Resource Management Academic Research Society (HRMARS), 2023)
Notwithstanding the prevalence of Autism in Malaysian society, addressing the outdated lack of data on the needed skills of therapy practitioners is needed as updated data implicates significant impacts beneficial to all parties. Providing the latest data also informs the specific actions needed to reduce Autistic-related problems in Malaysia. Hence, this study seeks to conduct a situational analysis of the needs of therapy practitioners at autism rehabilitation centres in Perlis. A qualitative survey method is used. Ten therapy practitioners from two autism rehabilitation centres in Perlis participated in the survey. Findings indicate that therapy practitioners require skills to communicate, socialise, provide treatments, teach, obtain knowledge, control emotions, and think. Additionally, reflex integration, speech therapy, handling behavioural cases, and hippotherapy are skills that participants have not learned but are considered essential in treating autistic children. Further, therapy practitioners stay in their profession because of their love for children, desire to improve skills and experience, contribution to the community, and religion. Several ongoing issues faced by parents with autistic children are children’s problematic behaviours, lack of time, knowledge, money, and difficulty communicating with their children. As for parental consciousness of the significance of rehabilitating their children, the result shows a high level of awareness. Implications from this research highlight the need for additional training for therapy practitioners to improve services and facilities to deal with autistic children at centres and motivate and guide parents using their practical knowledge to provide interventions at home.